Analysis of the Use of the Sipadu Application by Civil Servants in Manokwari Regency for Administrative Efficiency in Attendance Management - Tiara Yulesia Mahulette; Marlinda Sanglise; Lion Ferdinand Marini (International Journal Software Engineering and Computer Science (IJSECS), 2024)
This study aims to analyze the Sipadu application in the Manokwari Regency implemented by Civil Servants (PNS) to increase the administrative efficiency of absenteeism. Before the application came into action, absenteeism was controlled through attendance books or paper forms and everything took more time, then it was necessary to validate and adjust the data manually. The sheer volume of paper and equipment, managing, processing, and storing the attendance data also represented additional costs. The introduction of the Sipadu application shifted attendance recording from manual to automated system, so data entry and processing can be done in real time, paper and administrative equipment can be minimized, and the administrative process can be automated. According to the results of this study, attendance processing using the Sipadu application is faster, data accuracy is increased, and operational costs are reduced. Moreover, since there are automatic verifications in the application, the chances of repetition and tampering with data is reduced to keep the application transparent and reliable. Increasing employee satisfaction, as they are more focused on their activities no longer disturbed by absence input as a result of the benefits of implementing Sipadu linked with the attendance system that are efficient and transparent. This research shows that the Sipadu application as information technology solves the problems of absenteeism administration and public sector efficiency.